Integritas Kinerja Alumni: Respon Pengguna Alumni Institut Agama Islam Negeri Langsa Terhadap Kinerja berintegritas - yusaini, Yusaini; Sabaruddin, Sabaruddin; Darmawati, Darmawati (Program Studi Manajemen Pendidikan Islam IAIN Bone, 2022)
This article aims to describe the results of a user satisfaction survey on the integrity performance of IAIN Langsa graduates who work in government or private agencies, institutions, and organizations in Aceh Province. Performance with integrity is measured by the ability of graduates, which includes several aspects, namely discipline, honesty, work motivation, morality, and social skills. Performance with integrity is calculated using a survey questionnaire instrument tested for validity and reliability and distributed to IAIN Langsa graduates in Aceh Province users. Based on the results of data analysis using descriptive statistical test techniques, The users responded to all aspects measured by the integrity performance at the level of the category of satisfied and very disgusting. The research concluded that IAIN Langsa graduates have been able to produce performance with integrity which users rate as comfortable and very satisfying with an average percentage of 85%